Integrating declarative and imperative approach to model logistics service processes - Ying Wang; Lei Huang; Yi Guo (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: There is a widespread recognition of the importance of correctly modeling service processes as an effective way to provide a comprehensive understanding of the process and to enhance the service quality to clients. Taking this into account, this paper aims to construct the logistics service process model using the integration of the declarative approach and imperative approach. Design/methodology/approach: A methodology integrating the declarative and imperative process modeling approach is proposed for modeling the logistics service processes. Through investigation of the service departments and services involved, the process is decomposed into loosely-structured parts modeled by a declarative approach and highly structured parts modeled by an imperative approach. The loosely-structured and highly-structured parts are then integrated to form the model for the logistics service process. Findings: Through a case study for a Chinese bulk port, the integrative method proves to be effective in modeling the loosely-structured logistics service processes. The result model is able to express the logistics regulations and corresponding rules across different organizations as well as the strict execution order of the process activities inside a particular organization. Originality/value: The model could be the starting point for further logistics service process investigation. Future work could be conducted for conformance checking of the logistics service process using the model as a reference model.
Keywords: 650; logistics service process; process modeling; declarative approach; imperative approach